2020
DOI: 10.21315/aamj2020.25.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Factors of Consumers’ Purchase Intention Towards Life Insurance in Bangladesh: An Application of the Theory of Reasoned Action

Abstract: This study aims to examine the factors that influence consumer purchase intention towards life insurance. The study included religiosity, risk aversion motives, saving motives, and financial literacy with classical Theory of Reasoned Action (TRA), therefore extending the model. A convenience sampling method was employed to collect data from 315 respondents working in different public and private institutions in Bangladesh. Collected data were analysed using the structural equation model (SEM). The results reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 62 publications
1
21
1
2
Order By: Relevance
“…For example, an individual might think what the outcome of his decision will be and, based on his behavioral belief, he will decide whether to involve himself in a behavior or not (Ajzen, 1991). Attitude is an aspect of human beings that is linked to their minds and it provides them with a reason to form an intention or behavior (Arif, 2016; Nomi and Sabbir, 2020).…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, an individual might think what the outcome of his decision will be and, based on his behavioral belief, he will decide whether to involve himself in a behavior or not (Ajzen, 1991). Attitude is an aspect of human beings that is linked to their minds and it provides them with a reason to form an intention or behavior (Arif, 2016; Nomi and Sabbir, 2020).…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…For example, an individual might think of what others might expect from him or what others will think about him if he makes a certain decision. Subjective norm can also be defined as social pressure that an individual has from the people around him and this pressure guides him to perform or avoid a certain type of behavior (Tuan and Vinh, 2016; Nomi and Sabbir, 2020).…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Krajaechun and Praditbatuga ( 2019 ) articulated their results using Pearson's correlation coefficient, showing the acceptability of non-life insurance conditions and subjective normative attitudes toward the product were significantly associated with the intention to purchase non-life insurance. Nomi and Sabbir ( 2020 ) examined individual-level factors to explain changes in intention to purchase life insurance, empirically testing TRA as valuable. Um and Yoon ( 2021 ) argued that attitudes influence the intention to protect and participate in responsible tourism.…”
Section: Theoretical Model Construction and Research Hypothesesmentioning
confidence: 99%
“…Um and Yoon ( 2021 ) argued that attitudes influence the intention to protect and participate in responsible tourism. Nomi and Sabbir ( 2020 ) found that attitudes and subjective norms have the greatest impact on purchase intentions.…”
Section: Theoretical Model Construction and Research Hypothesesmentioning
confidence: 99%